The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0102-695x2010000300002
|View full text |Cite
|
Sign up to set email alerts
|

Chemotaxonomic significance of flavonoids, coumarins and triterpenes of Augusta longifolia (Spreng.) Rehder, Rubiaceae-Ixoroideae, with new insights about its systematic position within the family

Abstract: RESUMO: "Significância quimiotaxômica de flavonoides, cumarinas e triterpenos de Augusta longifolia (Spreng.) Rehder, Rubiaceae-Ixoroideae, com novos entendimentos sobre a posição sistemática dentro da família". Augusta tem sido tradicionalmente colocada na tribo Rondeletieae, Cinchonoideae subfamília. No entanto, recentes filogenias moleculares posicionou-a perto de Wendlandia, porém localizando A. longifolia perto do clado Ixoroidinae II. O estudo de A. longifolia resultou em duas cumarinas, cinco flavonoide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
5
0
1
Order By: Relevance
“…This coincidence between molecular phylogeny and other analyses such as flavonoids content (with its sub-groups, flavonol and flavone), other factors related to flavonoids production (ABA-sucrose–PAL activity) and gene expression suggests that phylogeny can predict flavonoids content. The agreement of the present molecular data with secondary metabolites (flavonoids) has been approved in several studies, including Choze et al ( 2010 ), Fico et al ( 2003 ), and Wollenweber et al ( 2003 ), which showed that at different hierarchical levels, the occurrence and distribution patterns of flavonoids mostly confirm newer molecular findings. Moreover, Kharazian, ( 2014 ) revealed that the chemical diversity of flavonoid profiles in 14 Salvia species (flavones, flavonols, flavanones, isoflavones, dihydroflavonols, and chalcones) can be used to assess the taxonomic status of the Salvia genus and that flavonoids are suitable indicators.…”
Section: Discussionsupporting
confidence: 87%
“…This coincidence between molecular phylogeny and other analyses such as flavonoids content (with its sub-groups, flavonol and flavone), other factors related to flavonoids production (ABA-sucrose–PAL activity) and gene expression suggests that phylogeny can predict flavonoids content. The agreement of the present molecular data with secondary metabolites (flavonoids) has been approved in several studies, including Choze et al ( 2010 ), Fico et al ( 2003 ), and Wollenweber et al ( 2003 ), which showed that at different hierarchical levels, the occurrence and distribution patterns of flavonoids mostly confirm newer molecular findings. Moreover, Kharazian, ( 2014 ) revealed that the chemical diversity of flavonoid profiles in 14 Salvia species (flavones, flavonols, flavanones, isoflavones, dihydroflavonols, and chalcones) can be used to assess the taxonomic status of the Salvia genus and that flavonoids are suitable indicators.…”
Section: Discussionsupporting
confidence: 87%
“…Geniposidic acid (MM = 374, C 16 H 22 O 10 , Table 1 ), showed signals at 397 [M + Na] + , 373 [M − H] − , 409 [M + Cl] − , 379 [M + Na − H 2 O] + , 217 [M + Na − H 2 O − Glc] + , 210 [M − H − Glc] − , 172 [M + Na − H 2 O − Glc − CO 2 ] + , 166 [M − H − Glc − CO 2 ] − , 148 [M − H − Glc − CO 2 − H 2 O] − , 122 [M − H − Glc − C 3 H 4 O 3 ] − . It is a iridoid already identified in fruit of Gardenia jasminoides Ellis (Rubiaceae) [ 19 , 22 , 31 , 32 ] and Wendlandia formosana Cowan leaves [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Tarenoside (MM = 358, C 16 H 25 O 9 , Table 1 ): showed signals at 357 [M − H] − ; 393 [M + Cl] − , 194 [M − H − Glc] − . This compound is an iridoid already identified in Wendlandia formosana Cowan leaves and Genipa americana [ 2 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Todos esses compostos estão sendo relatados pela primeira vez no gênero Sabicea e na tribo Sabiceae, porém, na subfamília Ixoroideae há relatos do isolamento da escopoletina de Augusta longifolia, 20 do ácido 5-O-cafeoilquínico e ácidos 3,5-e 4,5-O-dicafeoilquínico de Coffea arabica, 21 além do triterpeno ácido ursólico de Duroia macrophylla.…”
Section: Resultsunclassified